The I and the Body - Andrija Jurić (A Priori)
Abstract: In this paper, I shall try to present the dichotomy of the mind-body problem from the first-person perspective. The problem and the concept of the body itself are, perhaps, best shown through the philosophy of mind. One can argue that the concept is dialectically constructed in the history of philosophy in correlation and as opposed to the idea of the mind. Through the works of Avicenna, Descartes, Fichte, and others I will try to show that the idea of distinction is an epistemological one in nature. Descartes excludes everything not directly know as a certainty as not directly ‘himself’, thus concluding that he is a ‘thinking thing’, replacing the idea of himself as a corporeal thing with the idea of himself as a disembodied mind. From these kinds of ideas stems the original insight phrased in wording: “I know that I have a body” or question: “Are you a body with a mind or a mind with a body?”, differentiating that which knows (mind or subject) and that which is held (body or object). We can notice dualism in the very question: that which asks (the mind) and that with which that which asks is identified (the body). I shall argue that this direct cognitive accessibility and immediate self-consciousness are the reasons why we are able to distance “ourselves” from objects (in the end, our own body) by objectifying them in the process. And, at the same time, that the argument for the ontological difference is founded on the epistemological one, therefore, questioning its validity.